2004
DOI: 10.1159/000082278
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary Neurotrophic Factor Promotes Müller Glia Differentiation from the Postnatal Retinal Progenitor Pool

Abstract: Ciliary neurotrophic factor (CNTF) exhibits multiple biological effects during vertebrate retinal development, including regulating the differentiation of photoreceptor cells and promoting the survival and axonal growth of ganglion cells. We report here that in addition to affecting the differentiation of retinal neurons, CNTF also promotes Müller glia genesis in the postnatal mouse retina. In both retinal monolayer and explant cultures, CNTF increases the number of progenitor cells adopting the Müller cell fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 103 publications
3
31
0
Order By: Relevance
“…Moreover, we observed an increase in meteorin expression in CNTF-treated retinal explants, which induced Müller glia activation (supplementary material Fig. S3), confirming previous findings (Goureau et al, 2004). This result suggests that meteorin is upregulated in activated Müller cells.…”
Section: Meteorin Increases the Expression Of Gfap In Müller Glia In supporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, we observed an increase in meteorin expression in CNTF-treated retinal explants, which induced Müller glia activation (supplementary material Fig. S3), confirming previous findings (Goureau et al, 2004). This result suggests that meteorin is upregulated in activated Müller cells.…”
Section: Meteorin Increases the Expression Of Gfap In Müller Glia In supporting
confidence: 91%
“…6). These results also seem similar to the effect of CNTF on Müller glia (Goureau et al, 2004), which demonstrated that CNTF increases GFAP expression of Müller glia in P0 mouse retinal explant cultures, and at the same time, it increases the CRALBP-positive Müller glia cell population itself, indicating that CNTF is involved in differentiation of retinal precursor cells into Müller glia. However, we could not detect any change in Müller glial cell number in cultured retina either by meteorin or CNTF treatment.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…As a consequence of STAT activation, nascent photoreceptor cells may accumulate cytokine signaling inhibitors and thus become resistant to environmental cytokine as well as other STAT-activating signals to reach maturation and sustain their physiological function. Concomitantly, postmitotic Müller glia may require cytokine and other growth factor signaling to further differentiate and form the glial scaffold necessary for retinal structure and maintenance (Lillien, 1995;Lillien and Wancio, 1998;Goureau et al, 2004). The integration of intracellular signaling events triggered by various cell-extrinsic cues in progenitor cells and postmitotic cells may thus contribute to a balanced production of postnatal cell types and their proper differentiation.…”
Section: Discussionmentioning
confidence: 99%